An Approach for Evaluating External Wall-Roof Coupling Detail’s Performance - Türkay, Işıl; Altun, M. Cem (ICONARCH International Congress of Architecture and Planning, 2014)
Designing a coupling detail is a complicated job since coupling details are areas where building elements and other sub-systems come together and performances of single building elements come into a complex interaction. Mistakes in the design stage can lead to building failures after construction, which on the other hand are causing unhealthy environments and high repair or retrofitting costs. The intersection areas in the external envelope, exposed to environmental conditions, are even more vulnerable to building failures. Building element systems of the external envelope do have several functions. Some of them are in common, but some functions are differing. These common and/or varying functions are coupled at the intersection area, working independently, cooperatively or opposing. This is why a complex interaction is born in a coupling detail. The coupling area of the exterior wall system with the roof system is one of those intersection areas of the external envelope. It is obvious that a way to avoid building failures is proper detailing. In this paper, an approach to evaluate external wall-roof coupling detail’s performance is presented. The evaluation approach consists of two modules. The first module is a “performance requirements checklist” separately generated for each building element, namely; the exterior wall systems and the roof systems. The second module is a step-by-step evaluation tool for coupling details. The tool and the checklists are prepared by taking into consideration of sole functional continuity at coupling details, supported by material continuity and geometric precautions. The evaluation tool can be used either in the detail design process or before the tendering process for finalized details. The usability of the proposed approach is demonstrated through its application on a real world problem and pros and cons of the approach are discussed in conclusion.